Endoscopic Per-oral Pyloromyotomy for Gastroparesis: Initial Experience and Postoperative Comparison to Predicted Complications Following Laparoscopic Pyloromyotomy as Calculated by the ACS Risk Calculator. Issue 2 (15th April 2021) - Ward, Marc A.; Hasan, Salman S.; Whitfield, Edward P.; Ogola, Gerald O.; Leeds, Steven G.
Abstract : Introduction: Per-oral endoscopic pyloromyotomy (POP) is a promising new therapy in the treatment of gastroparesis, where the pyloric muscle is cut using an endoscopic tunneling technique. This study was designed to report outcomes from our initial experience and compare the rate of complications to the laparoscopic equivalent using the American College of Surgeons (ACS) risk calculator. Methods: Patients who underwent POP between August 2018 to May 2019 were prospectively followed in a database approved by the institutional review board. Preoperatively, patients were evaluated objectively with a 4-hour gastric emptying study (GES). Following POP, all patients were invited for repeat GES 3 months postoperatively. The same cohort was entered into the ACS risk calculator using laparoscopic pyloromyotomy (LPM) as the selected procedure. Complication risk of LPM was then compared with the actual complication rate of POP. Results: There were 11 patients that met study criteria (median age 52). Sixty-four percent (7/11) of patients agreed to do repeat GES postoperatively. Of those, 6 of 7 (86%) had normal GES (<10% emptying at 4 h) and the mean improvement was 36.4%. All patients were entered into the ACS risk calculator in which LPM (CPT code 43800) was used as a control. The postoperative complication rate was less than the median predicted risk of LPM in all categories including overall complications (0% vs. 10.05%), return to the operating room, (0% vs. 2.68%), and sepsis (0% vs. 1.42%). The rate of readmission (9% vs. 6.29%, P =0.65) was higher in the POP group than LPM predicted. Length of stay for all patients was significantly shorter than predicted (1.8 vs. 4.6 d, P <0.001). Conclusions: All POP patients had objective improvement in their GES and 86% had normal GES following this procedure. POP had significantly lower morbidity and reduced length of stay compared with that predicted of the laparoscopic equivalent using the ACS risk calculator.